Transcatheter Mitral Valve Replacement: slow and steady progress - Muller, David W. M. (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
In contrast to the exponential growth of transcatheter therapies performed for the treatment of aortic valve stenosis, transcatheter treatment of mitral valve regurgitation (MR) has moved relatively slowly from concept to clinical reality.